2014
DOI: 10.1371/journal.pone.0086132
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and Survival Rates of the Hawai’i Island Associated Spinner Dolphin (Stenella longirostris) Stock

Abstract: Reliable population estimates are critical to implement effective management strategies. The Hawai’i Island spinner dolphin (Stenella longirostris) is a genetically distinct stock that displays a rigid daily behavioural pattern, foraging offshore at night and resting in sheltered bays during the day. Consequently, they are exposed to frequent human interactions and disturbance. We estimated population parameters of this spinner dolphin stock using a systematic sampling design and capture–recapture models. From… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
106
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 72 publications
(114 citation statements)
references
References 45 publications
5
106
2
1
Order By: Relevance
“…Visual vessel based surveys were carried out on a monthly schedule to generate a robust estimation of dolphin abundance spending two days in Bay 1 and Bay 3 and four days in Bay 2 and Bay 4 each month (see Tyne et al (2014) and Tyne et al (2016) for more information). Weather permitting, information was collected at the top of the hour during hourly vessel scans between 07:00 and 16:00, including the presence/absence of dolphins, an estimation of the group size and the number of motorized vessels including the research vessel in the bay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Visual vessel based surveys were carried out on a monthly schedule to generate a robust estimation of dolphin abundance spending two days in Bay 1 and Bay 3 and four days in Bay 2 and Bay 4 each month (see Tyne et al (2014) and Tyne et al (2016) for more information). Weather permitting, information was collected at the top of the hour during hourly vessel scans between 07:00 and 16:00, including the presence/absence of dolphins, an estimation of the group size and the number of motorized vessels including the research vessel in the bay.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, in this study we moved under the surface with passive acoustic monitors to assess the potential acoustic response of Hawaiian spinner dolphins to the presence of human activities in four well-studied resting bays (e.g. Norris et al (1994); Östman-Lind (2009); Tyne et al (2014); Tyne et al (2016)). Given the importance of sound and these bays for these dolphins, assessing the potential acoustic response to human presence in these areas is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Scientific research has revealed the real impact that human activities are having on local spinner dolphin populations (Courbis and Timmel, 2009;Tyne et al, 2014). A proposed rule has been in the pipeline since an ANPR was issued by NMFS in December 2005 (NOAA, 2005).…”
Section: Federal Regulations Addressing Marine Mammal Harassmentmentioning
confidence: 99%
“…In Hawaii, spinner dolphins live in small (Tyne et al 2014) , isolated stocks with restricted ranges (Andrews et al, 2010) and have evolved a specialised behavioural ecology (Norris and Dohl 1980). They forage cooperatively offshore at night, and return to sheltered bays to socialise and rest during the day (Norris and Dohl 1980;Norris et al 1994;Benoit-Bird and Au 2009;Tyne et al 2015) during which time the bays are also used extensively by people for tourism, recreational and subsistence purposes (Heenehan et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Here, data from a rigorous photo-identification study designed to estimate abundance were used to provide a second consecutive annual abundance estimate for the Hawaii Island spinner dolphin stock (see Tyne et al 2014 for the first estimate) and evaluate the power of different sampling strategies to detect change in abundance. Five scenarios with different levels of sampling effort, based on the systematic approach employed in Tyne et al (2014), were evaluated in terms of their efficacy to detect trends in abundance by varying sampling effort, the rate of change in abundance, precision, power and the interval between annual abundance estimates.…”
Section: Introductionmentioning
confidence: 99%